2017
DOI: 10.1177/0271678x17699224
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrase inhibitors modify intracellular pH transients and contractions of rat middle cerebral arteries during CO2/HCO3 fluctuations

Abstract: The CO/HCO buffer minimizes pH changes in response to acid-base loads, HCO provides substrate for Na,HCO-cotransporters and Cl/HCO-exchangers, and H and HCO modify vasomotor responses during acid-base disturbances. We show here that rat middle cerebral arteries express cytosolic, mitochondrial, extracellular, and secreted carbonic anhydrase isoforms that catalyze equilibration of the CO/HCO buffer. Switching from CO/HCO-free to CO/HCO-containing extracellular solution results in initial intracellular acidifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 60 publications
2
35
0
Order By: Relevance
“…The current study adds to our growing appreciation that acid-base equivalents, and HCO 3 – in particular, fulfill multifaceted functions ( Boedtkjer et al, 2016a ). In cerebral resistance arteries, HCO 3 – (a) contributes to buffering of acute acid loads ( Rasmussen and Boedtkjer, 2018 ), (b) serves as substrate particularly for the Na + ,HCO 3 – -cotransporter NBCn1 that protects against intracellular acidification ( Thomsen et al, 2014 ), and (c) is sensed by RPTPγ to regulate cerebral perfusion ( Figure 6 ). In migrating vascular smooth muscle cells from conduit arteries, the high spatial mobility of the CO 2 /HCO 3 – buffer system also contributes to dissipating local pH gradients in diffusion-restricted spaces of filopodia ( Boedtkjer et al, 2016b ).…”
Section: Discussionmentioning
confidence: 99%
“…The current study adds to our growing appreciation that acid-base equivalents, and HCO 3 – in particular, fulfill multifaceted functions ( Boedtkjer et al, 2016a ). In cerebral resistance arteries, HCO 3 – (a) contributes to buffering of acute acid loads ( Rasmussen and Boedtkjer, 2018 ), (b) serves as substrate particularly for the Na + ,HCO 3 – -cotransporter NBCn1 that protects against intracellular acidification ( Thomsen et al, 2014 ), and (c) is sensed by RPTPγ to regulate cerebral perfusion ( Figure 6 ). In migrating vascular smooth muscle cells from conduit arteries, the high spatial mobility of the CO 2 /HCO 3 – buffer system also contributes to dissipating local pH gradients in diffusion-restricted spaces of filopodia ( Boedtkjer et al, 2016b ).…”
Section: Discussionmentioning
confidence: 99%
“…Immunocytochemical experiments demonstrated that astrocytes and neurons express the mitochondrial CA VA suggesting that this isozyme has a cell-specific, physiological role in the nervous system [28]. There is instead a lack of studies on CA VB in the brain, although it was recently detected in rat middle cerebral arteries [29]. CA VII is endowed with a good CO 2 hydrase activity and CA VIII is instead acatalytic—the two isoforms show comparable expression in the cortex, hippocampus and thalamus [30,31].…”
Section: Carbonic Anhydrases In the Central Nervous Systemmentioning
confidence: 99%
“…With regard to brain vessel wall effects, a recent study by Rasmussen and colleagues on isolated rat middle cerebral arteries showed that switching from CO 2 /HCO 3 − free to CO 2 /HCO 3 − containing bath solution at a fixed pH of 7.4 caused a biphasic pH response with initial acidification followed by a gradual recovery of pH and vasoconstriction [29]. In the presence of AAZ the rate of intracellular acidification and vasoconstriction were reduced, whereas applying the cell-impermeable CAI AMB (4-(aminomethyl)benzenesulfonamide) did not affect the rate of intracellular acidification.…”
Section: Effects Of Carbonic Anhydrases Inhibitors In Preclinical mentioning
confidence: 99%
See 1 more Smart Citation
“…Using out‐of‐equilibrium conditions – based on rapid mixing and laminar propulsion of solutions with differing H + /HCO 3 – /CO 2 composition – separate signaling consequences of acid‐base equivalents have been identified in resistance arteries (Boedtkjer et al. ; Rasmussen and Boedtkjer ). The response of resistance arteries to extracellular acid‐base disturbances is complex (Boedtkjer ) and relies not only on sensing of extracellular H + but also on separate signaling effects of intracellular H + (Boedtkjer et al.…”
Section: Discussionmentioning
confidence: 99%